EFFECT OF LENDING PT. BPR MITRA DHANACESWARA TO INCREASE REVENUES TRADER SMALL AND MICRO (Case Study in PT. BPR Mitra Dhanaceswara) - Aulady, Rizky; Ekowati, Wiwik Hidajah (Jurnal Ilmiah Mahasiswa FEB, 2012)
Bank is a financial institution whose principal business is to collect funds and distribute  those funds back  into  the community in  the form of credit and to provide services  in payment traffic  and circulation.  To  facilitate  its operations, the bank established a branch in  the areas with  the aim of providing  bank services  to the community, especially  in economically weak. One of the  services performed by the bank is  lending to  the public.  Basically the  main function  of the credit  is  to  the fulfillment services to the needs of the community (to service the society) in order to encourage  and  expedite  trade, production  and services  even  consumption,  all of  it aimed to improve human life. This study aims to determine whether there is the effect of giving loans against income traders BPR micro and small enterprises. This research method  using  kuantitatif  descriptive  case study approach.  Having found  trader revenues and results obtained after borrowing money at BPR  it will be calculated  to find out whether there is the effect of giving loans against income traders BPR micro and small enterprises.  This calculation  itself will be  using 4  methods, namely, regression, product moment correlation, T test and F test Keywords: Income, Credit, BPR